2021
DOI: 10.1002/ejp.1818
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of stratified treatment for back pain in Danish primary care: A randomized controlled trial

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 53 publications
3
22
1
1
Order By: Relevance
“…Overall, positive experiences with the stratified approach of our model were reported from all three perspectives (i.e., patients, physiotherapists, dieticians), which on the one hand is in line with previous qualitative studies [ 4 , 5 , 8 ], but on the other hand is in contrast to the lack of (cost-)effectiveness found in our OCTOPuS-trial [ 9 , 10 ] and recent other trials on stratified exercise approaches [ 14 18 ]. Physiotherapists generally intended to continue providing this stratified approach after completion of the OCTOPuS-trial and both dieticians and physiotherapists were enthusiastic about combining their professional expertise for the ‘obesity subgroup’ to achieve the best outcomes for these patients.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, positive experiences with the stratified approach of our model were reported from all three perspectives (i.e., patients, physiotherapists, dieticians), which on the one hand is in line with previous qualitative studies [ 4 , 5 , 8 ], but on the other hand is in contrast to the lack of (cost-)effectiveness found in our OCTOPuS-trial [ 9 , 10 ] and recent other trials on stratified exercise approaches [ 14 18 ]. Physiotherapists generally intended to continue providing this stratified approach after completion of the OCTOPuS-trial and both dieticians and physiotherapists were enthusiastic about combining their professional expertise for the ‘obesity subgroup’ to achieve the best outcomes for these patients.…”
Section: Discussionsupporting
confidence: 90%
“…Our inconclusive result seems to be consistent with the scarce and conflicting evidence regarding the cost-effectiveness of stratified approaches of physical therapy, with two trials 32 , 48 concluding that stratified care can be cost-effective, three trials 27 , 28 , 30 , 31 concluding that stratified care is unlikely to be a cost-effective option, and a last study 49 concluding that it might be cost-effective for only one out of three subgroups, compared to usual physical therapy. These conflicting results may be indicative for stratified care having only negligible added value to current physical therapy at best, but differences across studies in country, setting, patients groups, and stratification tool could play a role as well.…”
Section: Discussionsupporting
confidence: 77%
“…As reported elsewhere, 21 we found no added value in terms of clinical outcomes of this stratified approach compared to usual exercise therapy. 25 This result aligns with that of multiple other trials in musculoskeletal patient groups, where stratified physical therapy appeared to have no added value, 26 , 27 , 28 , 29 , 30 , 31 with only one trial demonstrating a (minimal) effect of stratified physical therapy over usual care in low back pain. 32 It could be argued, however, that despite having no added value in terms of clinical outcomes, stratified exercise therapy approaches such as ours are potentially more efficient (i.e., similar effect in less consultations).…”
Section: Introductionsupporting
confidence: 81%
“…8 The initial trial conducted in United Kingdom found that riskstratified care reduced disability and decreased health care costs compared with usual care. 8 Subsequent randomized trials in the United States (ie, the MATCH and TARGET trials) 9,10 and Denmark 11 did not find this same benefit. Thus, whether risk-stratified care is scalable to health systems outside the United Kingdom remains a challenge for improving LBP outcomes.…”
Section: Introductionmentioning
confidence: 98%